AI 및 에듀테크를 활용한 초등수학 교수·학습 모형 탐색 - 이유진(Yujin Lee), 박주경(Jukyung Park), 황지남(Jinam Hwang), 여승현(Sheunghyun Yeo) (Suhak gyoyukak yeon-gu (Online), 2025)
본 연구는 초등학교 수학 수업에서 인공지능(AI) 및 에듀테크의 효과적인 활용을 위한 교수⋅학습 모형을 탐색하는 것을 목적으로 하였다. 이를 위해 AI 및 에듀테크가 적용된 수학 수업을 분석하고, 수업의 강조점에 따라 유형화한 후 각 유형별 수업 단계와 활동을 정리하여 교수⋅학습 모형을 도출하였다. 연구 결과, AI 및 에듀테크를 활용한 수학과 교수⋅학습 모형으로 수학적 탐구 중심 모형, 평가-피드백 중심 모형, 맞춤형 활동 중심 모형, 협력적 문제해결 중심 모형을 도출할 수 있었다. 또한 각 모형에 해당하는 수업 사례를 제시함으로써 AI 및 에듀테크를 효과적으로 적용할 수 있는 구체적인 실천 방안을 제안하였다. 이러한 연구 결과를 바탕으로 AI 및 에듀테크를 활용한 초등학교 수학 수업 설계에 대한 시사점을 제공하고자 하였다. This study aimed to explore effective teaching and learning models for utilizing artificial intelligence (AI) and educational technology (EdTech) in elementary mathematics instruction. To this end, mathematics lessons incorporating AI and EdTech were analyzed and categorized based on their instructional emphases, and the teaching stages and activities of each type were examined to derive corresponding instructional models. As a result, four models were identified: the mathematics inquiry model, the assessment-feedback model, the personalized learning model, and the collaborative problem-solving model. In addition, specific lesson examples were presented for each model to suggest practical strategies for effectively integrating AI and EdTech into mathematics lessons. Based on these findings, this study provides implications for designing AI- and EdTech-integrated mathematics lessons in elementary school contexts. KCI Citation Count: 0